COMPREHENSIVE APPROACH TO ASSESSING AND PREVENTING PRE-DEMENTIA COGNITIVE IMPAIRMENTS IN PRIMARY HEALTHCARE SETTINGS - Kamilova M.R., Rakhimbayeva G.S., Sobirova D.R. (Central Asian Journal of Medicine, 2025)
Cognitive decline preceding dementia, often termed mild cognitive impairment (MCI), represents a critical window for intervention. Early detection and proactive management in primary healthcare can significantly reduce the progression to full-blown dementia. This study explores a comprehensive strategy for identifying and managing pre-dementia cognitive disorders within the framework of primary healthcare, emphasizing both diagnostic tools and preventive interventions.